INDONESIAN UNIVERSITY PILOT TOEFL PREP COURSE: STUDENTS’ SUCCESSES AND INSTRUCTORS’ INSIGHTS - Shirley Baker; Topan Rahmatul Iman; Liska Novianti Paramitaswari; Fahmi Dwilaksono; Maya Fitriana; Wiren Wirentake; Riri Rimbun Anggih Chaidir; Sherry Camden-Anders (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
This research examined the impact of an Indonesian university Pilot TOEFL Prep Course created to address the test taking strategies content and Communicative Language Teaching (CLT) methods research gaps. Existing literature focuses on specific test-taking techniques, rather than specifically using CLT methods for teaching inclusive listening, structure, and reading test-taking strategies. Thirteen randomly selected students participated in the Prep Course. Nine lecturers collaboratively designed and taught test-taking strategies using lectures, vocabulary knowledge, small group sessions, practice materials, and motivational activities. A qualitative action research design integrated thematic analysis of Student and Lecturer Survey responses, and lecturer Daily Notations, with quantitative pre-and posttest data. Research questions sought to determine if the course: 1) recognizably developed student English skills, 2) improved student test scores, and 3) contributed to the lecturers’ expanded teaching methods. The triangulated data showed that students (69%) improved their posttest scores and increased their English competencies. Lecturers reported that the course design positively influenced their future pedagogical approaches. Recommendations included developing two skill level classes, and longer courses with extended class times for all university students. The research offered data that contributes valuable insights for the TESOL/TOEFL fields and provides reasoning for future university English course options.